Evaluation of Trichoderma, Psedomonos and biofertisol as foliar application on quality and yield of guava (Psidium guajava) (Current Horticulture, 2024)
The experiment was designed in Randomized Block Design in four replications with seven treatments, i.e. T1 - control (only water),  T2 –Trichoderma viride 5%, T3-Trichoderma viride 10%, T4 - Pseudomonas 5%, T5 -Pseudomonas 10%, T6 -biofertisol 5% and T7 -  biofertisol 10%, at Department of Horticulture, JNKVV, Jabalpur, in 8 year old guava (Psidium guajava L.) variety L 49, during 2020- 21 and 2021-22. Foliar application of Trichoderma @ 10 % was most beneficial for growth, yield and quality parameters. Trichoderma  @ 10 % recorded maximum increment in shoot length, plant height, canopy height, leaf chlorophyll Index, chlorophyll content index,  LAI. Foliar application of 10% Trichoderma wasalso superior in yield parameter found maximum number of flowers shoot, fruit set  percentage, fruit retention percentage, fruits/shoot, fruit/splant, yield/plant, fruit length, fruit width, fruit weight, fruit volume,  pulp weight/fruit and pulp per cent. Total soluble solids, total sugar, and reducing sugar were recorded in Trichoderma 10% (T7) and  minimum acidity was recorded in foliar application of Pseudomonas 10% (T5) .
Keywords: Biofertilizer; Biofertisol; Pseudomonas; Trichoderma